The Effectiveness of Progressive Muscle Relaxation on Reducing Joint Pain in the Elderly at Jember Nursing Home : Efektivitas Relaksasi Otot Progresif Terhadap Penurunan Skala Nyeri Sendi pada Lansia di UPT PSTW Jember - Rahayu, Sri Puji; Putri, Galuh Yulia Asmara; Ferdiana, Intan Nahdia; Syafriansyah, Fahmi Essa; Rohmah, Siti Nailatul; Susumaningrum, Latifa Aini; Kurdi, Fahruddin (Jurnal Kesehatan Komunitas Indonesia, 2022)
Increasing age and the aging process can cause various problems, especially physical dissatisfaction, which results in impaired musculoskeletal function, namely joint pain which makes the elderly experience problems in carrying out daily activities. Pain management with non-pharmacological nursing actions that can be used to relieve joint pain in the elderly, namely progressive muscle relaxation therapy (ROP). This study aims to determine the impact of progressive muscle relaxation (ROP) on joint pain in the elderly at Wisma Melati UPT PSTW Jember. This research was conducted quantitatively with the type of quasi-experimental research using a research design approach (one group pre-test and post-test design). Samples were taken by purposive sampling. The sample population used in this study was elderly at Wisma Melati UPT PSTW Jember, with nine elderly people selected. The results showed that the respondents who took part were on average 77.11 years old (SD=5.732), the youngest was 70 years old and the oldest was 90 years old. The average value of the pain scale before performing progressive muscle relaxation (ROP) is 3.44 with a minimum value of 2 and a maximum value of 5. The mean value of the pain scale after administration of progressive muscle relaxation (ROP) is 2.67 with a minimum value of 0 (no pain) and the maximum value is 5. Based on the results of the analysis test using the t-test paired sample test the results of the joint pain scale before and after progressive muscle relaxation (ROP) was carried out, namely 0.0023 (p <0.005). There was a change or difference in the decrease in pain scale before and after giving progressive muscle relaxation therapy (ROP) to the elderly.